Teenage Pregnancy in Rural Indonesia: Does Education Level Have a Role? - Wulandari, Ratna Dwi; Laksono, Agung Dwi; Matahari, Ratu (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Teenage pregnancy is a high-risk pregnancy. Teenage pregnancy often gets social sanctions in the form of stigma from the community, and the loss of school rights. Objective: The research aims to analyze the role of education in teenage pregnancy in rural Indonesia. Methods: This study analyzed the data from the Indonesian Demographic and Health Survey 2017 using a cross-sectional approach. The unit of analysis was women aged 19-24 years old. The study pooled 1,982 women as samples. Besides the education level, other independent variables analyzed were marital, employment, and wealth. In the final stage of the study, a multivariate test with binary logistic regression was carried out. Results: The results showed that women with secondary education were 0.451 times less likely to experience teenage pregnancy than women with primary education (95% CI 0.354-0.574). Higher education was 0.110 times less likely to experience teenage pregnancy than primary education (95% CI 0.070-0.171). The study found two other variables related to teenage pregnancy in rural Indonesia besides educational factors. The two variables are employment status and wealth status. Conclusion: The study concluded that education level is associated with teenage pregnancy in Indonesia's rural areas. The lower the education level, the higher the chances of experiencing teenage pregnancy.